Floret farm's discovering dahlias ebook A guide to growing and arranging magnificent blooms. - Benzakein, Erin (2021)
A stunning guide to growing, harvesting, and arranging gorgeous dahlia blooms from celebrated farmer-florist and New York Times bestselling author Erin Benzakein, founder of Floret Flower Farm. World-renowned flower farmer and floral designer Erin Benzakein reveals all the secrets to growing, cultivating, and arranging gorgeous dahlias. These coveted floral treasures come in a dazzling range of colors, sizes, and forms, with enough variety for virtually every garden space and personal preference, making them one of the most beloved flowers for arrangements. In these pages, readers will discover: • Expert advice for planting, harvesting, and arranging garden-fresh dahlias • A simple-to-follow overview of the dahlia classification system • An A–Z guide with photos and descriptions of more than 350 varieties • Step-by-step how-to's for designing show-stopping dahlia bouquets that elevate any occasion Expert Author : Erin Benzakein's gorgeous flowers are celebrated throughout the world. Her book Floret Farm's A Year in Flowers was a New York Times bestseller and her first book, Floret Farm's Cut Flower Garden , won the American Horticultural Society Book Award. Filled with Wisdom : Overflowing with hundreds of lush photographs and invaluable advice, DISCOVERING DAHLIAS is an essential resource for gardeners and a must-have for anyone who loves flowers, including flower lovers, avid and novice gardeners, floral designers, florists, small farmers, stylists, and designers.